EFEKTIVITAS PEMBELAJARAN TEKNIK CERITA PEMULA DISKUSI TERHADAP KEMAMPUAN MENANGGAPI ISI ARTIKEL OLEH SISWA KELAS X SMA NEGERI 1 LUMBAN JULU TAHUN PEMBELAJARAN 2012/2013 - Santi Manurung (Fakultas Bahasa dan Seni, 2012)
This research aims to describe the relationship of experience writing on thebulletin board with the ability to write a narrative essay. This research wasconducted at the High School Student Park field totaling 128 students. Samplestaken as many as 32 students with a random sampling technique. This researchmethod is descriptive correlational study. Data collection tool that is used todetermine the experience of writing on the bulletin board in the form ofquestionnaires as many as 20 questions, while for the show to know the students'ability to write a narrative used in the form of essay tests. To find a researchhypothesis about the relationship experience with the Wall Magazine Writing onWriting Narrative Writing Ability to use product moment correlation formula.From the results of research conducted found that the experience of writing on thebulletin board by high school students of class X Terrain Park Student learning in2012/2013 and categorized both average = 68.44 and the ability to write anarrative essay categorized either by the average value of 75, 06. Furthermore, totest the normality of the variables X = 8.49, while for the variable Y = 5.88, thus itcan be concluded that the distribution of the data both variables were normallydistributed. Furthermore, from the calculation of research has been done usingproduct moment correlation formula, the working hypothesis (Ha) that states thereis a significant relationship between experience Writing in the Wall with AbilityMagazine Writing Narrative Writing by Students of Class X High School StudentPark Field Learning Year 2012/2013 can be acceptable for calculating r> r table(0.822> 0.349). At the 5% significance level.keyword, writing experience, a wall magazine, narrative essay.